Preoperative methylprednisolone does not reduce loss of knee-extension strength after total knee arthroplasty: A randomized, double-blind, placebo-controlled trial of 61 patients. (3rd September 2017) - Lindberg-Larsen, Viktoria; Bandholm, Thomas Q; Zilmer, Camilla K; Bagger, Jens; Hornsleth, Mette; Kehlet, Henrik
Abstract : Background and purpose — Patients undergoing total knee arthroplasty (TKA) face challenges related to postoperative reduction in knee-extension strength. We evaluated whether inhibition of the inflammatory response by a single preoperative dose of methylprednisolone (MP) reduces the pronounced loss of knee-extension strength at discharge after fast-track TKA. Patients and methods — 70 patients undergoing elective unilateral TKA were randomized (1:1) to preoperative intravenous (IV) MP 125 mg (group MP) or isotonic saline IV (group C). All procedures were performed under spinal anesthesia without tourniquet, and with a standardized multimodal analgesic regime. The primary outcome was change in knee-extension strength from baseline to 48 hours postoperatively. Secondary outcomes were knee joint circumference, functional performance using the Timed Up and Go (TUG) test, pain during the aforementioned tests, rescue analgesic requirements, and plasma C-reactive protein (CRP) changes. Results — 61 patients completed the follow-up. The loss in quadriceps muscle strength was similar between groups; group MP 1.04 (0.22–1.91) Nm/kg (–89%) vs. group C 1.02 (0.22–1.57) Nm/kg (–88%). Also between-group differences were similar for knee circumference, TUG test, and pain scores. MP reduced the inflammatory response (CRP) at 24 hours postoperatively; group MP 33 (IQR 21–50) mg/L vs. group C 72 (IQR 58–92) mg/L (p < 0.001), and 48 hours postoperatively; group MP 83 (IQR 56–125) mg/L vs. group C 192 (IQR 147–265) mg/L (p < 0.001), respectively. Interpretation — Preoperative systemic administration of MP 125 mg did not reduce the pronounced loss of knee-extension strength or other functional outcomes at discharge after fast-track TKA despite a reduced systemic inflammatory response.